Comparison of two methods for demodulation of pulse signals – application in case of central sleep apnea - Ronan, Le Page; Vinh, Nguyen Quang; Jean-Marc, Goujon; Luiz, Poffo; Monique, Thual (Vietnam Journal of Science and Technology, 2020)
In the field of 24/7 human health monitoring, pervasive computing makes possible the continuous analysis of physiological parameters from an ambulatory device with a great acceptability. This paper presents two methods for obtaining cardiac and respiratory rates from a single arterial pressure signal: AM-FM demodulation and Singular Spectrum Analysis (SSA). With the aim to monitor sleep apnea, two simulated central sleep apnea were performed and recorded with Biopac reference system. The results showed a good evaluation of the cardiac rate with Singular Spectrum Analysis and bad results with AM-FM demodulation. For the respiration rate, some other signals were tested with average results for both methods. Further experiments will deal with real sleep apnea cases and algorithm improvements.